Severe Metformin poisoning; Experience at a tertiary care hospital in Sri Lanka: a case series - P. W. M. S. S. Sirisena; N. M. Hettiarachchi; S. R. Manilgama; T. W. P. K. Thenuwara (Sri Lanka College of Internal Medicine, 2022)
Metformin is the first line medication used for the treatment of type 2 diabetes mellitus worldwide. It has been considered a cost effective and safe drug for decades. Though, lactic acidosis is a recognized adverse effect of metformin, it is sparsely seen with therapeutic doses. However, it occurs frequently in patients with metformin overdose and in the presence of renal insufficiency. Metformin associated lactic acidosis (MALA) carries a mortality rate of almost 50%. Early initiation of renal replacement therapy has shown to reduce morbidity and mortality in these patients. Metformin overdose is relatively uncommon and only few cases of severe metformin overdose are reported in the literature. Here, we discuss five cases of MALA due to severe metformin poisoning. Four of them were successfully treated with early use of renal replacement therapy.